Perforations of Gastro Intestinal Tract in Neonates: A Retrospective Study of Aetiological Factors Excluding Necrotising Enterocolitis - Saravanan Natarajan; Shankar Mohan; Sulthana Dhilras; Jameel Ahmed; Selvakumar Mariappan (EL-Med-Pub, 2019)
Background: Perforations of the Gastro Intestinal Tract (PGIT) in neonates, postnatally, apart from Necrotising Enterocolitis (NEC) as aetiological factor, though less common, are well known. Materials and Methods: Neonates presenting with PGIT, excluding NEC, were analyzed in this retrospective study, over a period of three years in a tertiary care centre. Results: Of 20 neonates presented with PGIT, during study tenure, 8 were due to non-NEC related causes. The site of perforation was stomach, ileum, cecum, colon, and rectum. The usual causes of PGIT in the neonates were spontaneous perforations and perforations secondary to mechanical obstruction. Patients underwent surgery with good outcome. Conclusions: PGIT in neonates due to aetiological factors apart from NEC, have better outcome, than those with NEC. The other causes of PGIT are spontaneous perforation, intestinal atresia, Hirschsprung's disease, anorectal malformations etc.